Diseño e implementación de un banco de pruebas y calibración para el sensor de nivel de líquidos VL53L5CX. (2023)
This degree project had as focus to design and implement a testing bench and calibration system for the liquid level sensor Vl53l5CX, with the aim of integrating this functionality into a device developed by WX Medtech S.A.S. The implementation involved utilizing the I2C serial protocol to communicate with a STMicroelectronics microcontroller, specifically the STM32F401 model, responsible for processing captured data essential for measuring various liquid levels.